Рациональное распределение тепловой нагрузки в теплофикационной установке турбины Т-100/120-130 - Шубенко, Александр Леонидович; Бабенко, О. А.; Голощапов, Владимир Николаевич; Козлоков, А. Ю. (НТУ "ХПИ", 2014)
В работе решена важная научно-техническая задача повышения эффективности эксплуатации теплофикационных турбин ТЭЦ. Показано, что рациональное распределение тепловой нагрузки между подогревателями сетевой воды нижней и верхней ступеней в зависимости от температуры наружного воздуха позволяет выработать дополнительную электрическую мощность при сохранении режима работы энергоблока.

This scientific paper is devoted to the improvement of the operation modes of the extraction turbines of heat power plants, which is possible due to the selection of rational methods for heating the network water. To solve this problem we used the mathematical model “SCAT”, which was developed by the Institute for the Mechanical Engineering Problems of the National Academy of Sciences of Ukraine. The purpose of this scientific paper is to increase the efficiency of the power–generating units of the heat power plant through the improvement of heat release modes. It has been shown that the rational distribution of the heat load between the network heaters of the lower and upper stages depending on the temperature of outdoor air allows for the generation of additional electric power maintaining the operation mode of power generating unit.
Rational distribution of thermal load in the heating plant of the turbine T-100/120-130
Keywords: теплофикационная турбина; сетевой подогреватель; электрическая мощность; heat power plant; extraction turbine; network heater; thermal loading; electric power